2018
DOI: 10.2139/ssrn.3296072
|View full text |Cite
|
Sign up to set email alerts
|

Female Labour Force Participation in Indonesia: Why Has it Stalled

Abstract: This paper examines the drivers of female labour force participation in Indonesia and disentangles the factors that have contributed to it remaining largely unchanged for two decades at around 51%. Data from the National Socioeconomic Survey (Susenas) and the Village Potential Statistics (Podes) over the period 1996 to 2013 are used to implement a cohort analysis which separates out life-cycle effects from changes over time in women's labour market participation. We find that the raw labour market participatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 8 publications
1
10
0
Order By: Relevance
“…13 participation (Lain, Alatas, and Setyonaluri 2020). This aligns with existing evidence at the desa/kelurahan (rural/ urban villages) level from Cameron, Contreras Suarez, and Rowell (2019).…”
Section: June 2021supporting
confidence: 90%
“…13 participation (Lain, Alatas, and Setyonaluri 2020). This aligns with existing evidence at the desa/kelurahan (rural/ urban villages) level from Cameron, Contreras Suarez, and Rowell (2019).…”
Section: June 2021supporting
confidence: 90%
“…The qualitative component aims to complement th quantitative study by providing an explanation for the findings. In particular, it attempts to assess the quantitative findings against a specific subsample of women who were identified to be the most vulnerable to leaving the labour force, namely working women who had recently given birth to their first child (Cameron and Contreras Suarez 2018;Lu et al 2017). Such findings would particularly be relevant in crafting policies which enforce stability in women's participation in the labour force regardless of their life pha ses.…”
Section: Empirical Strategymentioning
confidence: 99%
“…Halim et al (2019) find that an additional increase in public preschool in Indonesia could boost the labour participation of mothers with preschool-age children by 7.1 percentage points. Policies focusing on childcare services, flexible working conditions, and parttime work schemes might encourage more women to remain in the labour force after they marry or start a family (Cameron et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Blau and Kahn (2017) specified on the effect of the gender wage gap on female participation for the USA for the period 1980-10 and data from PSID 5 and CPS 6 and suggested that higher experience, education and union coverage elimination played a major role in the reduction of the gender wage gap, which showed a negative effect of 14.32. Finally, Cameron et al (2020) studied the Indonesian case with data from SUSENAS 7 and PODES 8 for the years 1996-13 and a cohort effect analysis in order to find effect magnitudes between 13-27 per cent, depending on the selected household and labour market characteristics.…”
Section: Empirical Studies On Female Participation In the Labour Marketmentioning
confidence: 99%